P-245 What itch do we need to scratch? nursing home education delivered by hospices. Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - Harding, Rebecca; Hill, Sarah
Abstract : Aim: End of life care needs to be delivered in a range of care settings with hospice professionals key to promote best practice influencing knowledge, attitudes and behaviours to other healthcare organisations (Hospice UK, 2017). Education and training is key to building these foundations (National Palliative and End of Life Care Partnership, 2015).This study focuses on describing what palliative care education is needed for nurses in nursing homes and does it differ to community nurses' education needs? Method: All nursing homes covered by a Hospice Outreach Nurse Team (HONT) were asked to participate in the study. Questionnaires with a combination of multiple choice questions and free text answers were sent to all nursing homes. Nursing home managers were contacted and permission given before questionnaires sent. The HONT hand-delivered or posted questionnaires with them returned/posted back after six weeks. Results: Questionnaires were sent to 17 Nursing Homes with a return rate of 78% of the total questionnaires sent. 71% were registered nurses; only the registered nurse data was collated. Length of time in current post was included with the majority in post for 3 years+ (66%). Most nurses described themselves as confident and/or competent in palliative care. Respondents replied that core subjects on the current education programme delivered to community nurses by the HONT would improve their care. 65% of responses stated they had completed palliative care training before with 35% acknowledging they had had no palliative training of any description. Only 10% indicated they had completed a university level training in palliative care. Conclusions and recommendations: Nurses in nursing homes want education which deals with broad subjects rather than anything specific. There was a global tone for training rather than specific areas – which suggests that a separate teaching programme is required for nursing home staff.